Mengkaji Peran Input Komprehensif dalam Kelas EFL Vokasional Tata Boga melalui Teks Prosedur: Menelaah Peran Input yang Mudah Dipahami dalam Kelas Bahasa Inggris sebagai Bahasa Asing (EFL) Kejuruan Kuliner dengan Menggunakan Teks Prosedur - Keisha Lingga Kusumadewi; Alief Noor Farida (Language Development Center, 2026)
Background: Focusing on Stephen Krashen’s Input Hypothesis, the study examines how teacher provides comprehensible input, students’ perceptions, and challenges that constrain the input of English for Specific Purposes (ESP) in culinary settings. Purpose: This study aims to explore the role of comprehensible input used by English teacher in culinary vocational EFL classroom through the use of procedure texts, shows students perspective about comprehensible input and its relevance, and analyzes the challenges encountered in applying the frameworks. Method: The research design that used for this study is a qualitative classroom-based case study. The research sets in SMK Ibu Kartini Semarang and use the participation from one culinary classroom and one English teacher. The data collection from this research was obtained through classroom observation, documents analysis, a survey form, and semi structured interview with teacher and selected students. Results and Discussion: The findings of the research shows that comprehensible input was primarily obtained through the interaction in classroom rather than instructional lesson plan, with frequent strategies used by the teacher such as simplification and repetition, translanguaging, visual support, and comprehension check in lesson. Students’ perception shows that they understand English in procedure text better through demonstrations, contextualized culinary tasks, and mixed-language during classroom. However, challenges exist from limited and unfamiliar vocabulary, time constraints, and variations of student’s proficiency levels. Conclusions and Implications: These findings indicates that comprehensible input in culinary EFL settings mostly supported through multimodal materials and interactive learning classroom.